Human Capital Accumulation in Post-green Revolution Pakistan: Some Preliminary Results (The Distinguishedl Lecture) (The Pakistan Development Review, 1989)
In this paper, I present some preliminary findings of a large and complex micro-economic research project. Work on the project, "Human Capital Accumulation in Post-green Revolution Rural Pakistan", began roughly two years ago. Most of the time since then, however, has been devoted to project design, to the administration of the Pakistan Survey of Rural Education, Migration and Employment (PSREME) and to the entry, cleaning and evaluation of the data generated by the survey. The research team has only just begun the fust phase of the econometric analysis of the data. The analytic work programme is scheduled to take another two and a half years to complete, hence my stress on the preliminary nature of the findings I present here. As the work programme progresses these fmdings will undoubtedly be refined, and in some instances substantially altered. There is a tension between the understandable desire of policy-makers to have research results "yesterday" and the laudable tendency among academics to ensure that they have got their analysis just right. With a project such as this one it takes a long time to do that. ·It is not that economists are inefficient producers of knowledge. Rather, despite technological advances that have had a marked impact on our productivity over the last two decades, micro economic research involving primary data collection and analysis remains an extremely time intensive activity. When particularly exasperated at how long a project is taking, I have been known to exclaim "I did not intend to become an economic historian."